Meeting in the Palacio Nacional: First day of the New Economy. F.l.t.r.: ?, ?, ?, Companys, Puíg Elias, ?. Copied from CNT collection
Meeting in the Palacio Nacional: First day of the New Economy. F.l.t.r.: ?, ?, ?, Companys, Puíg Elias, ?. Copied from CNT collection.